Evaluasi Layanan BK dalam Mendukung Pengembangan Peserta Didik Secara Optimal di SMPIT Widya Duta - Mubarokah, Afifatul Laila; Dewi, Adila Safana; Hidayat, Ade; Astuti, Pipit Puji; Azzam, Ariel Fadhilah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to evaluate the implementation of guidance and counseling (BK) at SMPIT Widya Duta, an integrated Islamic school in Bekasi City. The method used in this research is qualitative research. The data collection techniques were gathered through direct observation, semi-structured interviews with BK teachers and students, and documentation. The results show that BK services are structured based on the Service Implementation Plan (RPL) with a focus on four areas: personal, social, learning, and career, as well as individual counseling as the most preferred service. The results also indicate that the BK teacher's approach includes initial observation, peer strategies for introverted students, and enforcement of confidentiality, with stakeholder collaboration as a supporting factor. Recommendations that can be given to improve the effectiveness of BK services include collaborative interdisciplinary training, continuous evaluation, and technology integration to strengthen synergy between PAI teachers, BK, and parents to address operational challenges and optimize student learning comfort and character development.